2020
DOI: 10.3906/sag-1909-98
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of peritoneal dialysis patients: 9-year experience of a single centre in Turkey

Abstract: The prevalence of end-stage renal disease (ESRD) is increasing in the world [1,2]. Peritoneal dialysis (PD) has been an alternative treatment to hemodialysis (HD) for patients with ESRD since 1976 [3,4]. PD is a homebased treatment with many advantages; preservation of residual renal function (RRF), hemodynamic stability, better quality of life and cost savings [5][6][7][8]. Survival rates with PD are better than those with HD after 3 years from initiation [5,8,9]. Despite the advantages of PD in quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The discrepancy between our study and previous studies may be explained by distinct patient characteristics and different covariates included in the Cox proportional hazards model. Similar to the previous study, we also did not find diabetes to be a risk factor for technical failure, further affirming that diabetes should not be considered a hurdle for instituting peritoneal dialysis[ 11 - 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The discrepancy between our study and previous studies may be explained by distinct patient characteristics and different covariates included in the Cox proportional hazards model. Similar to the previous study, we also did not find diabetes to be a risk factor for technical failure, further affirming that diabetes should not be considered a hurdle for instituting peritoneal dialysis[ 11 - 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…The effect of DM on long-term prognostic outcomes of PDAP is controversial. A previous study found that DM is a risk factor for all-cause death[ 13 ]. Additionally, the study by Tsai et al[ 14 ] in a single Taiwan center also found a positive relation between DM and PDAP treatment failure, which was defined as death or catheter removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreting unadjusted survival rates might be misleading because patients' survival might decrease dramatically with comorbidities and other risk factors (e.g., age at PD initiation, nutritional status, clinical and biochemical outcomes such as hemoglobin level, and white blood cell count). For example, Turkey's five-year survival rates were reported as 36.8% and 79.8% in diabetic and nondiabetic subgroups, respectively, which was found to be significantly different [4].…”
Section: Introductionmentioning
confidence: 95%
“…According to Li et al [3], peritoneal dialysis use was estimated between 4% and 71.9%, and 5-year survival between 34% and 64% in different countries globally. In Turkey, Sipahioglu et al [2] estimated 5-year survival rates as 68.8%, and Tekkarismaz and Torun [4] estimated them as 65% in adults, which was higher than other regions reported by Li et al [3]. Interpreting unadjusted survival rates might be misleading because patients' survival might decrease dramatically with comorbidities and other risk factors (e.g., age at PD initiation, nutritional status, clinical and biochemical outcomes such as hemoglobin level, and white blood cell count).…”
Section: Introductionmentioning
confidence: 99%